2020
DOI: 10.1002/ccd.28824
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary trend of acute kidney injury incidence and incremental costs among US patients undergoing percutaneous coronary procedures

Abstract: Objectives: To assess national trends of acute kidney injury (AKI) incidence, incremental costs, risk factors, and readmissions among patients undergoing coronary angiography (CAG) and/or percutaneous coronary intervention (PCI) during 2012-2017. Background: AKI remains a serious complication for patients undergoing CAG/PCI. Evidence is lacking in contemporary AKI trends and its impact on hospital resource utilization. Methods: Patients who underwent CAG/PCI procedures in 749 hospitals were identified from Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…Thirty‐day readmission rates are a healthcare system performance measure determined by the Centers for Medicare and Medicaid Services due to rising healthcare costs. Previous research demonstrated higher rates of 30‐day readmissions in patients with AKI in the setting of PCI and TMVr 16,26 . In this study, 30‐day readmission was higher in patients with AKI associated with LAAC (18.1 vs. 9.7%).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Thirty‐day readmission rates are a healthcare system performance measure determined by the Centers for Medicare and Medicaid Services due to rising healthcare costs. Previous research demonstrated higher rates of 30‐day readmissions in patients with AKI in the setting of PCI and TMVr 16,26 . In this study, 30‐day readmission was higher in patients with AKI associated with LAAC (18.1 vs. 9.7%).…”
Section: Discussionmentioning
confidence: 43%
“…Previous research demonstrated higher rates of 30-day readmissions in patients with AKI in the setting of PCI and TMVr. 16,26 In this study, 30-day readmission was higher in patients with AKI associated with LAAC (18.1 vs. 9.7%). This higher rate of readmissions extended up to 180-days after discharge, with a large number of patients (45.7%) being readmitted after index discharge.…”
Section: Association Between Aki and Outcomes Following Laacmentioning
confidence: 53%
“…While beneficial for clinical interpretation and diagnosis, use of CM may result in adverse effects ( 1 ). One of the most important adverse effects associated with CM is contrast-associated acute kidney injury (CA-AKI) with incidence rates between 3 and 37% ( 2 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-associated acute kidney injury (CA-AKI) is a preventable complication of coronary angiography and percutaneous coronary intervention (PCI), 1 , 2 , 3 , 4 that has increased in incidence in recent years, is associated with increased hospital length of stay, readmission, and adverse cardiovascular and kidney outcomes, and increases costs of care by US $7000-$9000 per patient. 5 , 6 , 7 , 8 Although evidence indicates that minimizing the volume of iodinated radiocontrast media 9 , 10 , 11 , 12 , 13 and optimizing delivery of intravenous (IV) hydration 14 , 15 , 16 can prevent CA-AKI in patients at risk, 17 , 18 , 19 these strategies are used inconsistently in current clinical care. 1 , 20 , 21 Relatively little research has been done to determine how to better integrate these CA-AKI prevention strategies into clinical practice.…”
mentioning
confidence: 99%